ASSESSMENT OF FINANCIAL AND ECONOMIC LITERACY AMONG CZECH UNIVERSITY STUDENTS - Makovcová, Michaela; Dohnal, Ondřej; Čihák, Jakub; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
This bachelor thesis analyzes the level of financial and economic literacy among university students in the Czech Republic. The main contribution of the work is the creation of a set of questions that can be further used to measure financial and economic literacy. At the same time, the work presents a model that is suitable for evaluating tests focusing on financial and economic literacy (IRT model). From the application of CART analysis, it was not proven that the level of economic education achieved influences the level of financial or economic literacy of students. The reason may be insufficient application of economic and financial principles in practice.
Vedoucí práce: Ondřej Dohnal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses